Perkembangan Reksadana Syariah di Indonesia Tahun 2023: Pertumbuhan dan Tantangan - Budiani, Nur An-Nisa’ Aulia; Istichomah, nggit Putu; Putri, Zhenike Bubulia (CV. Civiliza Publishing, 2024)
Introduction/Main Objectives: The background of this study highlights the increasing awareness of the importance of investments aligned with Sharia principles, alongside challenges related to limited financial literacy in the Sharia domain. This research aims to analyze the development of Sharia mutual funds in Indonesia in 2023, which have experienced significant growth in line with rising public interest in Sharia-compliant investments. Research Methods: The study employs a qualitative approach by analyzing secondary data obtained from the Financial Services Authority (OJK) reports, relevant publications, and the latest statistical data. Finding/Results: The findings reveal that the net asset value of Sharia mutual funds reached IDR 42.78 trillion in 2023. This growth was driven by financial technology innovations and efforts to improve financial literacy among the public. Despite this positive trend, challenges persist, such as limited accessibility to products and inadequate public understanding of Sharia mutual funds. Conclusion: The study concludes that Sharia mutual funds hold substantial potential in supporting Indonesia's Sharia economy. However, more effective strategies are needed to enhance education and accessibility to Sharia-compliant financial products, thereby encouraging broader public participation in Sharia investments.